Governmental Accounting Maturity Toward IPSASs and the Approximation to National Accounts in the European Union. Issue 12 (14th October 2016) - Jorge, Susana Margarida; Jesus, Maria Antónia; Laureano, Raul M. S.
ABSTRACT: International Public Sector Accounting Standards (IPSASs) are a good reference for a harmonized microaccounting system allowing more transparency and quality in public sector accounting across EU member-States. However, questions remain concerning IPSASs contribution to the convergence between Governmental Accounting (GA) and the National Accounts (NA). This article assess how the proximity to an IPSAS-based accounting system in GA has impact on the diversity and materiality of GA-NA budgetary deficit/surplus adjustments, hence analyzing whether IPSASs might contribute to GA-NA reconciliation. Main findings show that IPSASs do not make considerable difference in terms of GA-NA adjustments, so IPSASs-based EPSASs will hardly contribute to approaching GA-NA.